Remarks on the genus Lipotactes Brunner v. W., 1898 (Orthoptera: Tettigoniidae: Lipotactinae) from China - Feng, Ji-Yuan; Zhou, Zhi-Jun; Cnang, Yan-Lin; Shi, Fu-Ming (Zootaxa, 2017)
The paper is a supplement of the genus Lipotactes Brunner v. W., 1898 (Orthoptera: Tettigoniidae: Lipotactinae) from China. We rechecked the specimens and distributions, provided the illustrations of important morphological characters of six species distributed in China, one of which, Lipotactes vietnamicus Gorochov, 1993 is firstly recorded from China, and the female of Lipotactes truncatus Shi & Li, 2009 is firstly described.